Modelling and Analyzing Turkish Business Cycles through Markov-Switching Models - Siklar, Emel; Siklar, Ilyas (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study uses the different versions of the Markov-Switching methodology for modeling business cycles in Turkey and determining their turning points through quarterly real GDP figures for the 1987-2021 period. Based on the results obtained from the models, the recovery periods in Turkey last approximately 8.5 quarters and exhibit long and permanent nature while contraction periods are short, variable, and temporary, lasting around 4 quarters on average. The estimated Markov-Switching models mostly produce the same turning points. The compatibility of the obtained results with the national and international developments experienced during the analyzing period indicates the consistency of the developed models. On the other hand, the results reveal the importance of consistent and credible monetary and fiscal policies in smoothing business cycles.